1991
DOI: 10.1109/14.83691
|View full text |Cite
|
Sign up to set email alerts
|

Observation of partial discharge in hexane under high magnification

Abstract: Partial discharges are observedin hexanes by means of shadow photography under the application of dc voltages. A nonuniform field geometry is employed and the growth of cavities associated with partial discharges at a point cathode is photographed at 200 x magnification. A multi-frame photograph of the cavity and a simultaneous record of the partial-discharge current provide a detailed record of the temporal and spatial development of the discharge. Examination of these data suggest that electrostatic forces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…Observation of streamer in hexane under both positive and negative DC voltages was reported in [14,15]. The results indicated that negative streamer current waveforms are more regular with an increasing pulse train and positive streamer current waveforms are less regular with intensive pulses superimposed on a continuous current [14,15]. Similar observations of current waveforms in a synthetic ester liquid under DC voltage was reported in [16].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Observation of streamer in hexane under both positive and negative DC voltages was reported in [14,15]. The results indicated that negative streamer current waveforms are more regular with an increasing pulse train and positive streamer current waveforms are less regular with intensive pulses superimposed on a continuous current [14,15]. Similar observations of current waveforms in a synthetic ester liquid under DC voltage was reported in [16].…”
Section: Introductionsupporting
confidence: 68%
“…There are limited publications comparing the streamer and breakdown phenomena between mineral oils and ester liquids under DC voltage as past studies focused on hydrocarbon liquids. Observation of streamer in hexane under both positive and negative DC voltages was reported in [14,15]. The results indicated that negative streamer current waveforms are more regular with an increasing pulse train and positive streamer current waveforms are less regular with intensive pulses superimposed on a continuous current [14,15].…”
Section: Introductionmentioning
confidence: 96%
“…Different techniques including discharge current measurement technique [4], ultra-high frequency (UHF) technique [3,5] and acoustic emission technique [2] were employed. Various insulating liquids including Hexane, mineral oil and semi-conductive nanofluids (SNFs) have been investigated in these papers.…”
Section: Introductionmentioning
confidence: 99%
“…Various insulating liquids including Hexane, mineral oil and semi-conductive nanofluids (SNFs) have been investigated in these papers. In [4], it described that the partial discharge current is in the form of a pulse train which is corresponding to the linear growth of the streamer. The streamer shape and stopping length in Hexane under dc stress have been studied in [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation